UJI BEBERAPA VARIETAS PADI SAWAH IRIGASI (Oryza sativa L.) DAN APLIKASI PUPUK KALIUM (KCl) UNTUK MENINGKATKAN PRODUKSI DAN KETAHANAN REBAH - Arnen Pasaribu; E Harso Kardhinata; Mbue Kata Bangun (Universitas Sumatera Utara, 2013)
Arnen Pasaribu, Test of Rice Varieties (Oryza sativa L.) and Fertilizing of Potassium (KCl) toIncrease Production and The Lodging Resistance. Ir. E.H. Kardhinata, M,Sc. as chairman of thecommision of advisors and members Ir. M.K. Bangun, MS. The aim of the research to get ricevarieties and the best dosage of potassium to increase production and the straw strenght.Randomized block designfactorial was used in this research. The first factors were the varieties(Ciherang, Inpari I, Mekongga and Cibogo) and second factors were dossages of potassium (0,50, 100, and 150 kg/ha). The treatments was used three replications. The parameter wichobserved are height of plant, straw strength, straw diameters, dry weight, straw thickness,panicle length, number of productive tillers, percentage of grains per penicle, percentage ofempty grains, the weight of 1000 seeds, weight of grains perplot, lodging index and hertability.The result of this experiment showed that weight of grains Ciherang is better than the others, themaximum dosages of potassium were 85.07 kg/ha; 103.35kg/ha and66.67 kg/ha for Ciherang,Mekongga and Cibogo but relation of potassium Inpari I showed linear positive. Interractions ofvariety and potassium showed significantly diffrence on height of plant at 3 week after plantedand weight of grains.Key words : Rice, Varieties, Potassium fertilizer.